Insights and use of medicinal plants in relieving respiratory affections among students: A case study from Guelma district (Algeria): A case study from Guelma district (Algeria) - Benhalima, Lamia; Amri, Sandra; Belhaoues, Saber; Oumeddour, Abdelkader (Ethnobotany Research and Applications, 2026)
Background: In Algeria, respiratory disorders remain the main causes prompting medical attention. In recent years, there has been a growing interest in herbal remedies, which play an essential role in the treatment of this kind of disease. In this context, this study was conducted to examine the awareness and the use of medicinal plants to relieve respiratory symptoms among university students in Guelma district, in northeastern Algeria. Methods: An ethnobotanical survey was conducted between December 2023 and May 2024 among 300 volunteered university students. The study explored students’ individual experiences in using of medicinal plants to relieve respiratory diseases and the source of their knowledge. Rao-Scott χ2 test and ethnobotanical parameters were used to analyze the data. Results: Findings showed that over 96% of students use at least three medicinal plants to treat respiratory system ailments. No difference was registered between exogenous and endogenous knowledge sources. Students identified 33 medicinal plants species classified under 17 families. Myrtaceae and Lamiaceae exhibited the highest family importance values. Syzygium aromaticum (L.) Merr. & L.M.Perry (RFC=0.52; UV=38.8) and Eucalyptus globulus Labill. (RFC=0.42; UV=40.7) being the most frequently employed species. Strong agreement among students and absolute fidelity levels (FL=100%) were recorded for several species used to manage respiratory ailments. Conclusions: The present study highlighted valuable information about students’ ethnopharmacological knowledge. However, proper training in this field, as well as exploration of the bioactive molecules of the species mentioned and assessment of their safety, are necessary. Keywords: Ethnobotanical data, Medicinal plants, Respiratory ailments, Students, Survey.